BARIERY W REFORMOWANIU SYSTEMU OPIEKI ZDROWOTNEJ W POLSCE - Redakcja (Wydział Prawa i Administracji UAM, 2002)
Health care has been founded on the priorities of accessibility and quality of health care services. It is also attempted to build an effective (also economically), just, and complex institutional system focused on health promotion and disease prevention, and at the same time allowing citizens a free choice o f medical services. The Author analyses the Polish healthcare system reform both from the perspective of global tendencies in healthcare systems and through the prism of domestic projects of organisation solutions that open the way to improving the work of medical institutions, rationalising the expenses and satisfying citizens’ medical needs. The strongly empirically oriented diagnosis of the difficulty to implement a new financial and organisational healthcare system provides information about the dysfunctional role played voluntarily or involuntarily by the reformers in building the social image of the changes in the healthcare system, the influence of the media on the public opinion concerning the healthcare reform, and finally the attitude to the reform of those addressed by it, i.e. medical workers and patients.
CHECKS ON THE POLISH HEALTHCARE REFORM